Utilization of SWOT Analysis, QSPM, SPACE to Determine Educational Strategy at Gabungan High School Jayapura - Sandra Titihalawa; Suwito Eko Pramono; Yeri Sutopo; Ida Zulaeha; Haryono Haryono (Universitas Negeri Semarang, 2023)
Gabungan High School is one of the oldest schools in Papua. A private school founded by the Protestant and Catholic Education Foundation under the auspices of two (2) churches, namely Protestant and Catholic. In its work in the world of education, the Jayapura Gabungan High School has also helped shape the nation's civilization. Around 75 years ago, at the start of the school's establishment, the Jayapura Combined Gabungan High School was an excellent school, had many enthusiasts, and had produced quality graduates such as ministers, governors and regents. However, the existence of the Gabungan High School did not last, when the government started building public schools, not only that, many private schools were built, this became a separate threat to the Gabungan High School. Through this research, do a strategy analysis that will be made by the school using the SWOT matrix, position and action evaluation (SPACE) strategy matrix, Grand Strategy Matrix and Quatitive Strategic Planning Matrix (QSPM) which begins with an analysis of the factors that have an impact on the school both from within and from outside school. The results obtained are 3 (three) strategic programs which are categorized as priority programs, namely 1) Schools build in collaboration with parents who have knowledge of administration to provide material for education staff; 2) Building cooperation with traditional parties to secure the school environment; and 3) Building alumni support.